The Use Of Guessing Game To Improve Students’ Speaking Skill Grade VIII At SMP NEGERI 12 Pematang Siantar (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
The use of guessing game to improve students’ speaking skill grade VIII at SMP Negeri 12 Pematangsiantar, Academic Year 2023/2024. Final Project. English Education Study Program. Faculty of Teacher Training and Education. Universitas Simalungun. A guessing game is a learning technique where a person or participants know something and then compete individually or in teams to identify or discover. The main problem in this study is whether there is an effect of using guessing games to improve speaking skills in learning on the learning outcomes of 8th grade students at SMP Negeri 12 Pematangsiantar.This research method uses the quasi experimental method with the type of two groups of pre-test and post-test. Design is a research method that uses two classes, namely the experimental class and the control class, which serves to determine the increase in student learning outcomes. Where the experimental class is given treatment with the guessing game learning model while the control class is given conventional learning treatment. The population of this study were all 8th grade students of SMP Negeri 12 Pematangsiantar. The sample in this study amounted to 62 people, where the control class (VIII-4) amounted to 31 people, and the experimental class (VIII-4) amounted to 31 people. The study was conducted for 6 meetings in each class group.Based on the results of the analysis data obtained, it can be said that tcount = 6.651> ttable = 1,697 at the significance level
Keywords: Guessing game; Speaking; Descriptive text